(untitled) (KYAMC Journal, 2017)
The Simultaneous occurrence of impacted 3rd Molar is a comon phenomana, observed in both side of Maxilla and Mandible. One of the common complication of impacted 3rd molar is pericoronitis. Here we report a 23 years old young female with pericoronitis (infection near wisdom teeth) in the left lower molar region. She attended to the Khwaja Yunus Ali Medical College and Hospital (KYAMCH) Dental Out Patient Department (OPD) with severe toothache and swelling at the left lower Retro Molar region. After clinical evaluation routine investigations and a Dental Radiograph (Periapical view) were advised. The Dental Radiograph showed a wisdom tooth, almost unerupted horizontally placed, surrounding soft tissue revealed features of inflammation. With all these data we confromed her diagnosis as pericoronitis in the left lower molar region that is Retro Molar region. Patient was prescribed a course of antibiotics and analgesics and sent home. Later on surgical procedure was parformed and the patient recoverd. This kind of patient needs regular followup for known post surgical complications like trismus, Bruising, persistent abscess etc. KYAMC Journal Vol. 5, No.-2, Jan 2015, Page 533-536